Unchanged trust in a time of change - Nyéki, Emőke; Juhász, Márta (Vezetéstudomány / Budapest Management Review, 2023)
The authors examined the behavior of managers during times of unexpected change. With their research, they looked for the answer to what managers should do so that employees would trust them. The authors anonymously and voluntarily asked 223 employees of 3 large manufacturing companies about their managers throughout the changes that occurred due to COVID-19, in contrast with the previously taken studies, during which a significant part of the research was carried out with unitarist practice using the only perspective seen from the perspective of management. It seems that the employees expect the number one leader to show direction and consider employee’s welfare to be equally important in such a period just as in any ordinary period. The direct manager’s sound judgment, competence, and professional competence is being evolved in unexpected situations. The authors draw attention to the need for individual treatment and the importance of managers’ „people management” skills.